Synthesis of Orthogonally Protected (2R,3R,4S)-4-Amino-2,3-dihydroxyheptane-1,7-dioic Acid - Tokairin, Yoshinori; Maita, Kakeru; Takeda, Sho; Konno, Hiroyuki (Synthesis, 2015)
(2R,3R,4S)-4-Amino-2,3-dihydroxyheptane-1,7-dioic acid, a common component of cyclic depsipeptide homophymines with anti-HIV activity, was synthesized as its orthogonally protected derivative from Fmoc-Glu(t-Bu)-OH in 6 steps. Osmium-catalyzed dihydroxylation of γ-amino-Z-α,β-unsaturated esters gave the dihydroxy esters with moderate diastereoselectivity. The stereochemistries of the amino acids were determined by comparison of 1H NMR spectra.
Keywords: unusual amino acid; dihydroxylation of Z-olefin; glutamic acid derivative; cyclic depsipeptide; JBCA method